RESULTS OF LONG-TERM OBSERVATIONS OF EARLY-TYPE STARS WITH CIRCUMSTELLAR SHELLS - Bergner, Yu. K.; Miroshnichenko, A. S.; Yudin, R. V.; Mukanov, D. B. (Одеські астрономічні публікації, 2017)
The results of UBVRIJHK photometric, RI polarimetric, and spectral observations of three Herbig Be stars MWC 137, MWC 297, and MWC 1080 are presented. Brightness variability and spectral features are analyzed. Evidences of cool star presence in MWC 297 are reported. Characteristics of central stars and their shells are estimated.